Analisis CP TP Dan ATP Di Gugus V Kecamatan Praya Tengah - Muh Hirkan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to determine the Analysis of CP TP and ATP of Islamic Education Teachers in Cluster V, Praya Tengah District. This study uses a qualitative phenomenological approach to build meaning based on field data. Data collection techniques use interviews, observations and documentation, while data analysis uses the flow model from Milles and Hubermant. The results of this study indicate that the way Islamic Education Teachers analyze CP, TP and ATP in Cluster V, Praya Tengah District is carried out with the following steps: Analyzing Learning Achievements (CP), Formulating Learning Objectives (TP), then Compiling Learning Objective Flow (ATP) so that from ATP learning steps will be compiled in the form of teaching modules/RPP